2015
DOI: 10.1515/pjst-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Ten Weeks Of Bodyweight Training On The Level Of Physical Fitness And Selected Parameters Of Body Composition In Women Aged 21-23 Years

Abstract: Introduction. The aim of the study was to assess the impact of 10 weeks of bodyweight training on selected elements of body composition (body mass, muscle mass, and the percentage of body fat and water) and components of physical fitness (strength, strength endurance, flexibility, and aerobic capacity) of women aged 21-23 years who do not practise sports professionally. Material and methods. The study involved 15 women whose mean age was 22 years 2 months. Their body mass and composition were assessed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
9
0
4
Order By: Relevance
“…For example, it has been shown that plyometric exercise as well as resistance exercise with slow movements can improve physical function in the elderly (Kikuchi & Nakazato, 2017;Watanabe et al, 2015). Moreover, 10 weeks of bodyweight training improved selected elements of body composition and components of physical fitness, including strength, flexibility and aerobic capacity, in sedentary 21-23-yr-old women (Lipecki & Rutowicz, 2015).…”
Section: Home-based Physical Activitymentioning
confidence: 99%
“…For example, it has been shown that plyometric exercise as well as resistance exercise with slow movements can improve physical function in the elderly (Kikuchi & Nakazato, 2017;Watanabe et al, 2015). Moreover, 10 weeks of bodyweight training improved selected elements of body composition and components of physical fitness, including strength, flexibility and aerobic capacity, in sedentary 21-23-yr-old women (Lipecki & Rutowicz, 2015).…”
Section: Home-based Physical Activitymentioning
confidence: 99%
“…Body-weight squats are known to benefit lower body strength and power. Such exercise can improve physical function in the elderly and enhance aerobic capacity and physical fitness (16)(17)(18). The recommended frequency of squat is 1-2 sets of 10 repetitions for the beginner and 2-3 sets of 20 repetitions for the advanced (4,19).…”
Section: Motion Analysis and Performance Feedbackmentioning
confidence: 99%
“…Kebugaran jasmani merupakan faktor utama yang mempengaruhi status kesehatan setiap individu [11]. Secara sederhana, kebugaran jasmani dapat dipahami sebagai kemampuan seseorang dalam melakukan suatu tugas gerak tertentu secara maksimal dan efisien tanpa mengalami kelelahan yang berlebihan serta terhindar dari resiko gangguan kesehatan [3].…”
Section: Pendahuluanunclassified